2006
DOI: 10.1152/ajpheart.01264.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucan phosphate attenuates cardiac dysfunction and inhibits cardiac MIF expression and apoptosis in septic mice

Abstract: . Glucan phosphate attenuates cardiac dysfunction and inhibits cardiac MIF expression and apoptosis in septic mice. Am J Physiol Heart Circ Physiol 291: H1910 -H1918, 2006. First published June 9, 2006 doi:10.1152/ajpheart.01264.2005.-Myocardial dysfunction is a major consequence of septic shock and contributes to the high mortality of sepsis. We have previously reported that glucan phosphate (GP) significantly increased survival in a murine model of cecal ligation and puncture (CLP)-induced sepsis. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(98 citation statements)
references
References 50 publications
4
93
0
1
Order By: Relevance
“…77,78 In line with these findings, the antiinflammatory mediator glucan phosphate, known to attenuate cardiac dysfunction and to improve survival rates in septic mice, has recently been shown to act by inhibiting the cardiac expression of MIF and reducing cardiomyocyte apoptosis. 79 Similarly, MIF has been shown to mediate the late and prolonged cardiac depression after burn injury associated with major tissue damage that was restored by anti-MIF treatment. 80 Notably, an increase in MIF within the alveolar space during late experimental sepsis or MIF instilled exogenously into the lungs induced kinase activation and phosphorylation in the heart, eg, of MAPK, as indicative of myocardial depression, suggesting that MIF released from the lungs during sepsis may in part be responsible for the cardiac dysfunction accompanying sepsis.…”
Section: Mif Contributes To Myocardial Dysfunction and Sepsismentioning
confidence: 99%
“…77,78 In line with these findings, the antiinflammatory mediator glucan phosphate, known to attenuate cardiac dysfunction and to improve survival rates in septic mice, has recently been shown to act by inhibiting the cardiac expression of MIF and reducing cardiomyocyte apoptosis. 79 Similarly, MIF has been shown to mediate the late and prolonged cardiac depression after burn injury associated with major tissue damage that was restored by anti-MIF treatment. 80 Notably, an increase in MIF within the alveolar space during late experimental sepsis or MIF instilled exogenously into the lungs induced kinase activation and phosphorylation in the heart, eg, of MAPK, as indicative of myocardial depression, suggesting that MIF released from the lungs during sepsis may in part be responsible for the cardiac dysfunction accompanying sepsis.…”
Section: Mif Contributes To Myocardial Dysfunction and Sepsismentioning
confidence: 99%
“…As an example, lipopolysaccharide (LPS) challenge results in significant cardiac dysfunction mediated by NF-B activation (12). We have previously reported that cardiac function was significantly depressed in CLPinduced septic mice (9). We also reported that administration of glucan phosphate (GP) significantly improved cardiac function in CLP sepsis (9) and increased long-term survival (30).…”
mentioning
confidence: 99%
“…Przeprowadzone dotychczas badania wskazują, że uszkodzenie serca wiąże się głównie ze zmianami czynnościowymi [15]. Mimo że stwierdzono na modelu zwierzęcym istotne zmiany apoptyczne włókien mięśniowych, praktyka kliniczna pokazuje, że występujące zaburzenia funkcji serca nie są adekwatne do tego typu zmian [13,16,17]. Prawdopodobnie dysfunkcja związana jest głównie z efektem cytokinowym i w znaczącym stopniu jest odwracalna.…”
Section: Histopathological Examinationunclassified
“…Studies conducted to date demonstrate that cardiac damage is mainly related to functional changes [15]. Although significant apoptotic lesions in muscle fibres have been shown in the animal model, clinical practice demonstrates that identified cardiac function disorders are not consistent with lesions of this type [13,16,17]. The dysfunction is probably linked to the cytokine effect and is largely reversible.…”
Section: Histopathological Examinationmentioning
confidence: 99%